Accessibility of employee assistance programme services to healthcare workers in a South African public hospital during the COVID-19 pandemic: a qualitative study - Mosanya, Letlhogonolo Koketso; Mabvurira, Vincent; Nkarenbi, Juliette Bih (Penerbit Universiti Kebangsaan Malaysia, 2025)
The onset of the Coronavirus (COVID-19) pandemic affected almost every facet of human life. This exerted a lot of pressure on healthcare workers, who became overwhelmed while having to protect themselves and their families from contracting the virus. In addition to protective clothing and other services, Employee Assistance Programs (EAPs) became crucial for healthcare workers as they faced psychosocial problems related to work. This study sought to explore the accessibility of EAP services to healthcare workers in a public hospital in the North West Province of South Africa, during the COVID-19 pandemic. The study was qualitative in nature, with semi-structured face-to-face interviews used to collect data from a sample of 9 nurses, 2 doctors and 3 social workers. The data was analysed thematically. The participants had varied responses on the accessibility of the EAP services. The study noted that healthcare workers had difficulties accessing the services or might not have accessed them at all. Additionally, the study found that employees who could have fully accessed services were those who tested positive for COVID-19, and as soon as they recovered, the services were discontinued. The research recommends that EAP policies be revisited to prepare them for the demands of future pandemics. Debriefing sessions for healthcare professionals and EAP practitioners should be normalised during instances of pandemics. In the event of future pandemics, new forms of communication and online services should be prioritised to host virtual sessions with healthcare workers.